CO2-philicity of crude oil constituents: A computational study - Lionel T. Fogang; Syed M.S. Hussain; Theis I. Solling (Chemical Thermodynamics and Thermal Analysis)
The present ab initio study has investigated the affinity of CO2 to various binding sites in molecules that consist of an aromatic ring with aliphatic substituents. The effect of unspecific solvation was included with a polarizable continuum model. In all cases, CO2 has the largest affinity towards the aromatic ring. This preference is small (free energy differences of less than 5 kJ mol−1). When evaluating the electronic interactions alone, that is using 0 K electronic energies, that complex consisting of CO2 adhering to the organic molecule is favoured. However, when including entropy effects, that is using 298.15 K free energies, the separated species become the most favourable combination. This highlights any subtle molecular-level interaction will not play a role in the context of oil reservoirs because they are usually warmer than 100 °C. Leaving computational uncertainties aside, the repulsive interactions align with the experimental observation of minimal CO2 solubility at room temperatures. Thus, the solubility that is relevant at reservoir conditions really is determined by bulk phenomena.